The Influence of Education and Training Program on Employee Performance At PT. Julia Multimedia Nusantara Makassar - Febrianti, Kirei; Aris Baharuddin; Nurhasni Muis (Fakultas Ilmu Sosial dan Hukum, 2025)
Knowledge and expertise are some of the factors that affect employee performance, to achieve company goals, employees must be able to meet these performance standards. Every company has a different way so that its employees can have the knowledge and skills needed to support the process of achieving company goals. This research was conducted to find out how the influence of education and training on employee performance at PT. Julia Multimedia Nusantara Makassar, partially or simultaneously.. This research is quantitative using multiple linear regression method, with the help of SPSS 25 software. This study uses a questionnaire as a data collection instrument. Data retrieval using a saturated sample technique because the population is less than 100, then all members of the population are used as samples, totaling 35 employees. The results showed that partially the education variable had no effect on employee performance, on the contrary the test results for the training variable showed that partially there was a significant effect on performance. While the education and training variables simultaneously have a significant effect on employee performance with a strong correlation level.